2010
DOI: 10.1007/s11701-010-0195-x
|View full text |Cite
|
Sign up to set email alerts
|

Robotic surgical management of endometrial cancer in octogenarians and nonagenarians: analysis of perioperative outcomes and review of the literature

Abstract: The primary aim of this article is to report the outcomes of octogenarians and nonagenarians who have undergone robotic surgery for endometrial cancer. A multi-institutional research consortium was created to evaluate the utility of robotics for gynecologic surgery (benign and malignant). IRB approval was obtained at each institution. A multi-institutional HIPPA compliant database was then created and analyzed for all patients that underwent robotic-assisted surgery with staging for endometrial cancer between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 21 publications
1
5
1
Order By: Relevance
“…Our results did not show a worsening of the surgical outcomes when the age increased, in agreement with Uccella et al who demonstrated the maintenance of an advantage of LS compared with laparotomy even in patients aged 80 years or older (6) and Lowe et al who showed a 96% successful robotic procedures in octogenarians and nonagenarians (33). Furthermore, although Walker et al showed an increased conversion rate (from LS to Laparotomy) for each decade of age (34), our analysis did not reveal any differences in the conversion rate according to the age class.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results did not show a worsening of the surgical outcomes when the age increased, in agreement with Uccella et al who demonstrated the maintenance of an advantage of LS compared with laparotomy even in patients aged 80 years or older (6) and Lowe et al who showed a 96% successful robotic procedures in octogenarians and nonagenarians (33). Furthermore, although Walker et al showed an increased conversion rate (from LS to Laparotomy) for each decade of age (34), our analysis did not reveal any differences in the conversion rate according to the age class.…”
Section: Discussionsupporting
confidence: 92%
“…who demonstrated the maintenance of an advantage of LS compared with laparotomy even in patients aged 80 years or older ( 6 ) and Lowe et al. who showed a 96% successful robotic procedures in octogenarians and nonagenarians ( 33 ). Furthermore, although Walker et al.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Lowe et al 22 published their findings on robotic surgery in the elderly in 2010, with data from a database set up by a multi-institutional research consortium over a 6 year period. They identified 27 patients aged 80 to 95 years who underwent robotic-assisted hysterectomy and staging for endometrial cancer and compared their perioperative outcomes to a younger group of 395 patients undergoing the same procedure for the same diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21] Robotic surgery has been shown to be safe and feasible in patients with endometrial cancer who are at higher risk for complications, such as obese and elderly women. 17,[22][23][24][25] Although robotic surgery is associated with a shorter hospital stay and fewer perioperative and postoperative complications, 26 we currently lack information regarding other elements of QoL that are important factors in a patient's preference for surgical approach. Because of the findings in the LAP2 study 27 that survival is not compromised by use of a minimally invasive approach for surgery in women with uterine cancer, QoL becomes a crucial factor influencing a patient's preference for surgical approach.…”
Section: Introductionmentioning
confidence: 99%